PERANCANGAN STRATEGI PEMASARAN UNTUK SECOND BRAND“SHINE” DI PT. TJAKRINDO MAS, SURABAYA - Marcell Suryansjah Juda; Markus Hartono; I Made Ronyastra (Perpustakaan Universitas Surabaya, 2018)
PT. Tjakrindo Mas, established in 1984, is a manufacture company in building material and office equipment, whose products are office furniture, office equipment, steel doors, PVC pipes, concrete pile, and wooden furniture. This company is ISO 9002 certified. The increasing number of office development in Surabaya has created good opportunity that is going to be seized by PT. Tjakrindo Mas. However, PT. Tjakrindo Mas is not the only company who sees the opportunity. Other companies also see the opportunity to increase sales. In this case, in order to compete with other companies and increase sales, a reasearch to formulate an appropriate strategy is required, it is necessary to have an adequate technology in production to be able to fulfil the demand of consumers in a short time and reduce the defective products to minimize the company’s loss. Information technology is also required in order to make it easier for the consumers to contract PT. Tjakrindo Mas or to order office equipment products. In collecting the data required by PT. Tjakrindo Mas, questionnaires were distributed, and analyzed using SPSS. From the SPSS test, it can be concluded that there was a difference between the data of the consumer’s reality level and consumers’s expectation level. SPSS, a SWOT, 4P strategy, and consumer’s behavior anlysis was also conducted to build a marketing strategy. Based on the data analysis, it is acknowledged that the criteria of product, price, process, brand element should be improved or should formulate new strategies. Marketing strategy design was also devided based on the criteria for the product category by suggesting plastic cabinet as a new innovation of PT. Tjakrindo Mas, creating the “SHINE” brand, providing a room for the consumers to see or take their own product, using wooden packaging in order to avoid defect. For the price category, a bundle price product was given for consumers who purchased products in high quatity. For the process category, an outsource fleet service was chosen so that the shipping could be on time, and information system was improved in the company to avoid out of stock. For the brand element categoty, a salesman is required to give the contact numbers to the distributors, give suggestions in symbol and brochure to give easier information to the consumers. Conducting a brand element analysis was also conducted because “SHINE” product is considered new. The purpose is to introduce the product to the consumers. It is also formulated based on the result of the questionnaire in order to archive a good and relevant result.